2009
DOI: 10.1071/ea08247
|View full text |Cite
|
Sign up to set email alerts
|

Genetics of adaptive traits in heifers and their relationship to growth, pubertal and carcass traits in two tropical beef cattle genotypes

Abstract: Abstract. Genetic analyses of tropical adaptive traits were conducted for two tropically adapted genotypes, Brahman (BRAH) and Tropical Composite (TCOMP). Traits included tick scores (TICK), faecal egg counts (EPG), buffalo fly-lesion scores (FLY), rectal temperatures under hot conditions (TEMP), coat scores (COAT), coat colour on a light to dark scale (COLOUR), navel scores (NAVEL) and temperament measured as flight time (FT). The data comprised adaptive measures recorded at specific times on 2071 heifers com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
58
4

Year Published

2009
2009
2020
2020

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 70 publications
(69 citation statements)
references
References 28 publications
(60 reference statements)
7
58
4
Order By: Relevance
“…The genetic correlation between tick and milk traits was negative with large standard errors, while the heritabilities of these traits were similar to previous estimates. Compared with previous estimates the heritability for tick burden in this study was larger than the value of h 2 = 0.15 found in zebu and zebu composite Brahman and Tropical Composite cattle for tick scores (Prayaga et al 2009), but similar to the value of h 2 = 0.41 AE 0.08 calculated for taurine cattle using multiple tick counts (Henshall 2004) and within the range of h 2 = 0.34-0.49 previously calculated for cattle in Queensland (Wharton et al 1970;Mackinnon et al 1991). Heritabilities for the milk yields were similar to previously estimated values for these traits (Pander et al 1992) but higher than previous estimates restricted to Australian Holstein and Jersey (Visscher and Goddard 1995).…”
Section: Discussioncontrasting
confidence: 43%
See 1 more Smart Citation
“…The genetic correlation between tick and milk traits was negative with large standard errors, while the heritabilities of these traits were similar to previous estimates. Compared with previous estimates the heritability for tick burden in this study was larger than the value of h 2 = 0.15 found in zebu and zebu composite Brahman and Tropical Composite cattle for tick scores (Prayaga et al 2009), but similar to the value of h 2 = 0.41 AE 0.08 calculated for taurine cattle using multiple tick counts (Henshall 2004) and within the range of h 2 = 0.34-0.49 previously calculated for cattle in Queensland (Wharton et al 1970;Mackinnon et al 1991). Heritabilities for the milk yields were similar to previously estimated values for these traits (Pander et al 1992) but higher than previous estimates restricted to Australian Holstein and Jersey (Visscher and Goddard 1995).…”
Section: Discussioncontrasting
confidence: 43%
“…In cattle, zebu have greater growth rates and performance in the presence of parasites, in hotter climates and fed lower quality feed than taurine animals, but poorer growth rates and performance in the absence of parasites, in cooler climates and fed better quality feed Vercoe 1977, 1984). However, these might represent breed genetic differences because genetic correlations for growth traits and parasite resistance traits are often close to zero when analysed within a breed (Prayaga and Henshall 2005;Prayaga et al 2009).…”
Section: Introductionmentioning
confidence: 99%
“…They indicated that most adaptive traits were moderately to highly heritable (Table 3). Their results were confirmed in a later, independent experiment undertaken in similar environments to the studies in the earlier review (Prayaga et al, 2009), indicating there is ample opportunity to improve these traits through selection, even though they are difficult to include in genetic evaluation systems because of their difficulty of measurement.…”
Section: Component Traits Of Female Reproductionmentioning
confidence: 55%
“…We used data from 866 cows representing 51 sire families from a tropical composite population bred in the tropical northern regions of Australia that was described elsewhere (5,9,(40)(41)(42). In these cows, 22 traits were annotated: AGECL (days), presence or absence of corpus luteum close to the day when bulls were placed in the same paddock as the heifers (CLJOIN, score 1-0), WTCL (kg), scanned P8 site fat depth at AGECL (FATCL, mm), PPAI (days), PPAI with respect to weaning time (PW, score 1-0), live weight (WT, kg), hip height (HH, cm), serum concentration of insulin-like growth factor I (IGF-I, ng/mL), average daily weight gain (ADG, kg/d), body condition score (CS, score 1-10), scanned longissimus dorsi area (SEMA, cm 2 ), scanned P8 site fat depth (SP8, mm) and scanned fat depth measured between the last 2 ribs (SRIB, mm).…”
Section: Methodsmentioning
confidence: 99%